Neutrality, fairness or freedom? Principles for platform regulation - Friso Bostoen (Internet Policy Review, 2018)
The need for online platform regulation has been a topic of scholarly debate. However, reality is now catching up to and even overtaking the academic writing on this subject. France has adopted a law on platform fairness, the European Commission recently ordered Google to implement a form of search neutrality, and more regulatory initiatives are on the horizon. That is why we have to look beyond the question whether online platforms should be regulated. As actual regulation supplants the scholarly debate, we must also examine how they are being regulated. This article distils from the various proposals at EU and member state level a set of operational principles that can serve as a frame of reference for productive debate on platform regulation.
Keywords: 300; Platforms; Regulation; Fairness; Neutrality; Transparency; Non-discrimination